Selected Benefits and Threats Arising from Internet use by Households and Enterprises in Poland with Respect to the COVID-19 Pandemic - Kisiel, Roman; Woźnialis, Greta (Olsztyn Economic Journal, 2021)
The internet has revolutionised the world over the past half of a century, and the COVID-19 pandemic has contributed to an increase in its importance. Although the global network brings with it more advantages than disadvantages, its existence also causes certain threats which have an impact on the life of Polish households and operations of Polish enterprises. This paper is theoretical and empirical in nature. Its aim is to explore the relationship between the internet and the COVID-19 pandemic, i.e. the time household members spend online. The impact of the two factors on survival in the market was examined in the case of enterprises. Moreover, the subjectively most important benefits and threats arising from the global network consumption in the opinion of the business entities mentioned above were illustrated. According to the respondents, facilitating communication is the main advantage of the internet (33.33%), whereas the spreading of hate on the internet is the major threat associated with its use (24.17%). The main benefit derived from the global network resources by enterprises is the possibility of obtaining raw materials from the most profitable sources (28.40%), whereas the major threat identified by them is that a negative opinion published on the internet can weaken the financial standing of a company or even make it disappear from the market (55.56%). Nearly 60% of household members found themselves spending more time online during the COVID-19 pandemic. Nearly 94% of the entrepreneurs who use the internet in running their businesses admitted that it helped them to keep their business in the market during the pandemic.